2005
DOI: 10.1128/jb.187.21.7243-7253.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Genome Evolution inListeria monocytogenes: the lmo0423 and lmo0422 Genes Encode σCand LstR, a Lineage II-Specific Heat Shock System

Abstract: Listeria monocytogenes strains belonging to phylogenetic lineage II (serotypes 1/2a, 1/2c, and 3a) carry a lineage-specific genome segment encoding a putative sigma subunit of RNA polymerase (lmo0423, herein referred to as sigC), a gene of unknown function (lmo0422) similar to the padR family of regulators, and a gene that is similar to the rodA-ftsW family of cell wall morphology genes (lmo0421). To understand the function of this set of genes, their expression patterns and the effects of null mutations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 68 publications
(66 reference statements)
3
56
1
Order By: Relevance
“…s M , s W and s X ), whereas in S. aureus, ECF s-factors are absent (Jordan et al, 2008). L. monocytogenes contains a single ECF s factor named s C (lmo0423), which has been shown to contribute to heat tolerance; however, no apparent link to the cell wall stress response has been observed (Zhang et al, 2005). The general stress sigma factor s B contributes to the tolerance of L. monocytogenes to cell-wall-acting antibiotics (Begley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…s M , s W and s X ), whereas in S. aureus, ECF s-factors are absent (Jordan et al, 2008). L. monocytogenes contains a single ECF s factor named s C (lmo0423), which has been shown to contribute to heat tolerance; however, no apparent link to the cell wall stress response has been observed (Zhang et al, 2005). The general stress sigma factor s B contributes to the tolerance of L. monocytogenes to cell-wall-acting antibiotics (Begley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…7. In addition, two gene clusters, one coding for a twin arginine secretion apparatus, TatAC (lmo0361-lmo0367), and the sigC gene cluster (lmo0421-lmo0423) (41), are lacking in the genome of L. welshimeri. It was previously reported that sigC codes for C , which is involved in thermal resistance specific for L. monocytogenes strains of phylogenetic lineage II (41).…”
Section: Vol 188 2006mentioning
confidence: 99%
“…In addition, two gene clusters, one coding for a twin arginine secretion apparatus, TatAC (lmo0361-lmo0367), and the sigC gene cluster (lmo0421-lmo0423) (41), are lacking in the genome of L. welshimeri. It was previously reported that sigC codes for C , which is involved in thermal resistance specific for L. monocytogenes strains of phylogenetic lineage II (41). When cultures of L. welshimeri, L. monocytogenes EGD-e, and L. innocua were assessed for survival following temperature upshift at 60°C for 0, 5, 10, and 15 min, only L. welshimeri was significantly impaired in its ability to recover from exposure to this nonpermissive temperature (see Fig.…”
Section: Vol 188 2006mentioning
confidence: 99%
“…However, AphA does not seem to be involved in phenolic acid metabolism in V. cholerae. More recently, the roles of two PadR-like repressors were reported for Listeria monocytogenes: LstR, which is required for effective thermal resistance (35), and LadR, the transcriptional regulator of the mdrL gene, which encodes a multidrug efflux transporter (15).…”
mentioning
confidence: 99%